Nutritional and Functional Bioactivity Value of Selected Azorean Macroalgae: Ulva compressa, Ulva rigida, Gelidium microdon, and Pterocladiella capillacea. Issue 7 (16th June 2017) - Paiva, Lisete; Lima, Elisabete; Neto, Ana Isabel; Marcone, Massimo; Baptista, José
Abstract: This study presents information on the biochemical composition (dry weight basis), nutritional aspects, and angiotensin I‐converting enzyme (ACE) inhibitory properties of selected macroalgae ( Ulva compressa, Ulva rigida, Gelidium microdon, and Pterocladiella capillacea ) from Azores. Moisture content was very high (83.2% to 90.0% of fresh weight). Total dietary fiber (33.7% to 41.0%) that presented a good balance of both soluble and insoluble fibers (15.5% to 19.2% and 18.2% to 21.8%, respectively) was the most abundant component in these macroalgae. Protein and ash (ranged from 15.7% to 23.4% and 10.7% to 20.7%, respectively) were the 2nd most abundant components in red and green macroalgae, respectively. Moderate soluble carbohydrate contents (14.5% to 19.8%) were found in all species. Lipid contents were low (1.0% to 4.3%), particularly in Ulva species (1.0% to 1.7%), but contained higher unsaturated fatty acids (FAs) (7.5% to 32.9% and 29.6% to 69.2% of total FA for monounsaturated fatty acid and polyunsaturated fatty acid groups, respectively) than saturated fatty acid (23.3% to 46.8% of total FA) contents. All the macroalgal proteins had high digestibility in vitro (82.2% to 89.4%, relatively to sodium caseinate), contained high quantity of essential amino acids (45.3% to 58.1% of total amino acids), but in different proportions, and were rich in aspartic and glutamic acids that together account for 17.2% to 36.2% of the total amino acids. These results suggested that regular consumption of the selected macroalgae may improve human health and revealed that they can be used for producing food supplements for human and animal nutrition and/or pharmaceuticals with potential effect on the regional economy. Furthermore, the ACE‐inhibitory IC50 values of 0.095 to 0.695 mg/mL for the <1 kDa protein hydrolysate fraction revealed a potential impact on hypertension disorder.